Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376
Keywords: Innovation ouverte; Laboratoire vivant; Living Labs; Mesure d'impact; Réservé UdeM

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
Number: 3 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
Number: 3 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376
Keywords: Innovation ouverte; Laboratoire vivant; Living Labs; Mesure d'impact; Réservé UdeM